Ética e nova condição comunicativa - Moser, Antônio (Revista eclesiástica brasileira, 2007)
From the 60s onward the Christian world got used to repeating an expression that, according to the II Vatican Council, defined what the world at the time was going through: “rapid and deep changes”. In theory, the definition continues to be true, but the expression no longer reflects either the speed or the depth of the changes operating today, only fifty years later. Under the sign of communications that are marked by both simpler and more complex revolutionary processes, is the human being him/herself who changes at a dazzling speed in the way s/he communicates, feels, thinks and is. Indeed the new communicative condition became the new human condition with all that means in terms of solutions and questionings.